Analisis Potensi Ekonomi Sektor Pertanian, Kehutanan, dan Perikanan di Kabupaten Mojokerto (Analysis of Economic Potential of the Agriculture, Forestry, and Fisheries Sectors in Mojokerto Regency) - Rozci, Fatchur; Romandani, Ida Wahyu (Jurnal Ilmiah Sosio Agribis, 2025)
This study analyzes the growth patterns and structural shifts of the agriculture, forestry, and fisheries subsectors in Mojokerto Regency for the 2013-2022 period using secondary GRDP data. The analytical methods applied are Klassen Typology and Shift Share. The results of the Klassen Typology identify the Food Crops and Forestry & Logging subsectors as advanced sectors. The Fisheries subsector is categorized as advanced but depressed, while the Plantation Crops and Livestock subsector is advanced but growing slowly. On the other hand, the Horticulture and Agricultural Services & Hunting subsectors are relatively lagging. The Shift Share analysis shows overall positive growth for the Mojokerto agriculture, forestry, and fisheries sector, indicating that its growth is faster than the average growth of similar sectors in East Java Province. In more detail, the Horticulture, Plantation Crops, Livestock, Agricultural Services & Hunting, Forestry & Logging, and Fisheries subsectors have positive proportional growth values, meaning their performance is better than similar subsectors at the provincial level. Furthermore, the Food Crops, Forestry & Logging, and Fisheries subsectors are competitive and highly competitive at the regional level. This study highlights variations in performance and competitiveness across subsectors, with Food Crops and Forestry/Logging leading the way, while Horticulture and Agricultural Services require more attention.Keywords: Agricultural Sector, Growth Pattern, Shift Pattern, Typology Klassen, Shift Share